(untitled) (Legal journal - Research in Legal and Social Sciences, 2020)
This research reflects the increase of the request for Psychological Assessments, filed at the Caaguazu’s Prosecution Office’s Victims Assistance Center, where it could be spotted that most of the people who attend the mentioned center are women, and the agressors, in turn, men; henceforth, there was the need to know the particular characteristics of the punishible offenses filed at the office. Consequently, the reference point was the statistical record for the period january to december 2018. At this juncture, it shows what is considered as “Violence against women”, together with the types of violence, the risk factors, and the psychological harms that can be done to the victims; besides, it could be detailed how these offenses occur in Caaguazu and the neighboring cities.